Microorganisms of the Phyllosphere: Origin, Transport, and Ecological Functions - Warren, Steven D. (Frontiers in Forests and Global Change, 2022)
Microbes are ubiquitous residents of the atmosphere, including the air that we breathe. They are also widely present in terrestrial, marine, and aquatic environments. Typical microbes include viruses, fungi, archaea, bacteria, algae, and bryophytes. Many are of edaphic origin and play significant ecological roles in the soil. Propagules are exceedingly lightweight and small, generally measured in microns (millionths of a meter). Propagules achieve airborne status in the wind, where they may travel from a few millimeters to thousands of kilometers. Most have been recorded at least as high as the stratosphere. While airborne, microbes may pass through multiple generations. Microbes in the atmosphere are often accompanied by vast clouds of dust. They perform a variety of essential functions such as raindrop and snowflake condensation nuclei, without which there would be little or no precipitation. It is important to realize that all solid things that are carried up into the atmosphere must eventually fall back down to the Earth. When precipitated or deposited back onto the Earth, they may land on and occupy any surface, including trees and other plants where they become epiphytic residents. They have been documented on broad-leaved and needle-leaved trees from deserts to tropical rainforests. If they land on bare soil, they often participate in biological soil crusts that are important for soil stabilization and for water and nutrient cycling.